Efficiencies of five arbuscular mycorrhizal fungi in alleviating salt stress of trifoliate orange - Ying-Ning, Z. (Yangtze Univ., Jingzhou (China). Coll. of Horticulture and Gardening); Qiang-Sheng, W. (Yangtze Univ., Jingzhou (China). Coll. of Horticulture and Gardening) (International journal of agriculture and biology, 2011)
Arbuscular mycorrhizal fungi (AMF) can enhance plant tolerance to salinity, while effects of dissimilar AMF on salt-stressed plants are unclear. This study was carried out to evaluate the efficiencies of five AMF species viz. Diversispora spurca (Preiff, Walker & Bloss) Walker and Schussler, Glomus etunicatum Becker and Gerdemann, G. mosseae (Nicol. & Gerde.) Gerdemann and Trappe, G. versiforme (Karsten) Berch and Paraglomus occultum (Walker) Morton and Redecker on growth, leaf relative water content (RWC), root architecture and sugar content of trifoliate orange [Poncirus trifoliata (L.) Raf.] seedlings subject to 100 mM NaCl. In saline soils, root mycorrhizal colonization and numbers of entry points, vesicles and arbuscules were as follows: G. versiforme greater than D. spurca greater than G. mosseae greater than P. occultum greater than G. etunicatum. All the fungi except G. etunicatum notably enhanced plant height, stem diameter, shoot, root and total dry weights and also partly or markedly improved root architecture, including number of root tip, length, surface area, projected area and volume. D. spurca, G. versiforme, G. mosseae and P. occultum abviously increased root sucrose, leaf and root glucose and allocation of sucrose to root, but decreased allocation of glucose to root. Leaf RWC was higher in mycorrhizal (except G. etunicatum) than in nonmycorrhizal seedlings. The results of the present study suggest that G. versiforme is the best effective mycorrhizal fungus in alleviating salt stress of trifoliate orange and G. etunicatum is the lowest effective mycorrhizal fungus.